GE_GERICHTE C/10211/2016 vom 9. Juni 2017 - GE Cour de justice (2017)
OBLIGATION D'ENTRETIEN ; ENFANT ; OBLIGATION D'ENTRETIEN ; CONJOINT ; REVENU HYPOTHÉTIQUE ; DÉBITEUR ; DIRECTIVE(INJONCTION) | CC.176.1; CC.285.1; CC.285.2;